Nalidixic acid potentiates the antitumor activity in sorafenib-resistant hepatocellular carcinoma via the tumor immune microenvironment analysis - Liu, Zhi-Yong; Zhang, Dan-Ying; Lin, Xia-Hui; Sun, Jia-Lei; Abuduwaili, Weinire; Zhang, Guang-Cong; Xu, Ru-Chen; Wang, Fu; Yu, Xiang-Nan; Shi, Xuan; Deng, Bin; Dong, Ling; et al. (Frontiers in Pharmacology, 2022)
Sorafenib resistance is often developed and impedes the benefits of clinical therapy in hepatocellular carcinoma (HCC) patients. However, the relationship between sorafenib resistance and tumor immune environment and adjuvant drugs for sorafenib-resistant HCC are not systemically identified. This study first analyzed the expression profiles of sorafenib-resistant HCC cells to explore immune cell infiltration levels and differentially expressed immune-related genes (DEIRGs). The prognostic value of DEIRGs was analyzed using Cox regression and Kaplan–Meier analysis based on The Cancer Genome Atlas. The primary immune cells infiltrated in sorafenib-resistant HCC mice were explored using flow cytometry (FCM). Finally, small-molecule drugs for sorafenib-resistant HCC treatment were screened and validated by experiments. The CIBERSORT algorithm and mice model showed that macrophages and neutrophils are highly infiltrated, while CD8+ T cells are downregulated in sorafenib-resistant HCC. Totally, 34 DEIRGs were obtained from sorafenib-resistant and control groups, which were highly enriched in immune-associated biological processes and pathways. NR6A1, CXCL5, C3, and TGFB1 were further identified as prognostic markers for HCC patients. Finally, nalidixic acid was identified as a promising antagonist for sorafenib-resistant HCC treatment. Collectively, our study reveals the tumor immune microenvironment changes and explores a promising adjuvant drug to overcome sorafenib resistance in HCC.